Parvalbumin-expressing interneurons coordinate hippocampal network dynamics required for memory consolidation - Nicolette Ognjanovski (Nature Portfolio, 2017)
Episodic memory consolidation requires activity in hippocampal area CA1. Here the authors report that pharmacogenetic inhibition of CA1 PV+ interneuron firing after fear learning blocks memory consolidation and disrupts associated enhancement in network oscillations and stabilization of functional connectivity patterns.